Analisis Faktor – faktor yang Mempengaruhi Konversi Lahan Karet Menjadi Kelapa Sawit di Kecamatan Sungai Gelam Kabupaten Muaro Jambi: Penelitian - Ashari Saad; Saidin Nainggolan; Zakky Fathoni (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the factors influencing farmers’ decisions to convert rubber plantations into oil palm plantations in Sungai Gelam Subdistrict, Muaro Jambi Regency. The issue arises due to the declining productivity and fluctuating price of rubber, while oil palm cultivation offers higher and more stable economic returns. The study used a survey method with a quantitative approach employing binary logistic regression analysis. A total of 85 farmer respondents were purposively selected. The variables analyzed include farming experience, product price, land ownership size, other income sources, pests and diseases, labor costs, and tapping frequency. The results showed that price, land ownership size, and tapping frequency significantly affected farmers’ decisions to convert rubber to oil palm, while the other variables were not significant. The Nagelkerke R² value of 0.76 indicates that 76% of the variation in conversion decisions is explained by the independent variables. Economic considerations are the main factor influencing conversion, as oil palm farming is perceived as more profitable, efficient, and stable compared to rubber farming.